Reduced Activity of HDAC3 and Increased Acetylation of Histones H3 in Peripheral Blood Mononuclear Cells of Patients with Rheumatoid Arthritis. (3rd October 2018) - Li, Yan; Zhou, Mi; Lv, Xiuying; Song, Lina; Zhang, Di; He, Yan; Wang, Mian; Zhao, Xue; Yuan, Xiaoqing; Shi, Guixiu; Wang, Dashan
Abstract : Aberrant histone acetylation and deacetylation are increasingly thought to play important roles in the pathogenesis of rheumatoid arthritis (RA). However, limited data from studies about the activity of histone deacetylases (HDACs) and histone acetyltransferase (HAT) in RA are controversial. Those conflicting results may be caused by sample size, medication, and age- and sex-matched controls. The aim of this study is to investigate the expression and activity of class I HDACs (1–3.8) and their effects on histone acetylation in peripheral blood mononuclear cells (PBMCs) from RA patients. The expression of class I HDACs in PBMCs from RA patients was decreased in both mRNA and protein levels in comparison with HCs. The nuclear HAT activities were dramatically increased. Further, we found HDAC3 activity to be the most significantly reduced in overall reduction of HDACs in the RA group. The extent of total histone H3, but not H4, acetylation in PBMCs from RA patients was increased compared to that in healthy controls (HCs) (p < 0.01 ). In RA PBMCs, the activity and expression of class I HDACs are decreased, which is accompanied with enhanced HAT activity. An altered balance between HDAC and HAT activity was found in RA PBMCs.